2011
DOI: 10.1002/aic.12729
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of oil flowability by assembly of comb‐type copolymers with paraffin and asphaltene

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Comb-type (maleic acid alkylamides-co--octadecene) copolymers (MACs) assemble with long-chain n-paraffins and asphaltenes by the hydrophobic alkyl branches and polar groups, respectively, and improve flowability of crude oils upon cooling. Their effects on the crystallization of paraffins from model oils were studied by rheology, optical microscopy, differential scanning calorimetry, and X-ray diffraction. Upon cooling, MACs change the size and shape of paraffin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…Figure 7 shows the synthesis route of poly(maleic anhydride amide co-a-olefin) (Xu et al 2009;Li et al 2012). …”
Section: Poly(maleic Anhydride Amide Co-a-olefin) (Mac)mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 shows the synthesis route of poly(maleic anhydride amide co-a-olefin) (Xu et al 2009;Li et al 2012). …”
Section: Poly(maleic Anhydride Amide Co-a-olefin) (Mac)mentioning
confidence: 99%
“…10 Chemical structure of ODMA asphaltene, MAC was proved to be more effective than PEB in improving the flowability. The interaction between the carboxyl and amide groups of MAC with the polar aromatic asphaltenes appears to stabilize crudes through the steric effect of the long alkyl groups Li et al 2012). …”
Section: Poly(maleic Anhydride Amide Co-a-olefin) (Mac)mentioning
confidence: 99%
“…Nowadays, blending crude oil with low concentration of polymer additives appears to be a more effective way of solving those problems caused by wax precipitation. Several kinds of comb‐type polymer additives such as poly(ethylene‐butene) (PEB) and poly(maleic anhydride ‐co‐α‐ olefin) derivatives (MAC) have been reported as cold flow improvers for waxy oil.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the experimental results, the assembly of comb‐type MACs with the paraffins and asphaltenes in the Liaohe extraheavy oils is proposed and is shown in Figure . The nonpolar alkyl pendants of the MACs could cocrystallize with long‐chain paraffins, whereas the polar groups covered the crystal surfaces and hindered the growth of crystals; this was indicated by the reduction of τ y , the smaller size of the paraffin crystals, and the lower T onset and Δ H Total . MACs with higher f values had more alkyl side chains; this should have made them more effective for cocrystallizing with paraffins.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we synthesized poly(maleic acid alkylamide‐ co ‐α‐octadecene) copolymers (MACs) . They significantly improved the flowability of model waxy oils and crude oils from the Halliburton and Tomark Industries . It has been found that the efficiency of MACs as a flow improver mainly depends on the composition of the oils and the polar/nonpolar group ratio of the polymer additives.…”
Section: Introductionmentioning
confidence: 99%